KOMPARASI KARAKTER PENGAYAAN LOGAM PADA DUA SEKSI PLUTON LASSI DI WILAYAH SOLOK, PROVINSI SUMATRA BARAT - Ronaldo Irzon; Mamat Suhermat; Hilman Suwargana; Kurnia; Windi Anarta Draniswari (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2023)
Intrusions in Sumatran are part of the granitoid range of Southeast Asia. The Volcanic Arc Suite is located in the western part of Sumatra and on the Bukit Barisan range. The intrusions in this province are unique because they are small pluton, including Pluton Lassi, unlike the intrusions in East Mandala and Central Mandala which are batholiths. Sumatra situated is in a tropical environment so it is vulnerable to weathering. This study aims to compare the impact of weathering on metal enrichment in two Pluton Lassi profiles from two different sections. The composition of each sample was analyzed using XRF and ICP-MS at the Center for Geological Survey. Fresh samples are classified as granodiorite based on microscopic analysis. Based on chemical analysis, the sample is diorite, high-K Alkaline Calc series, metaluminous, and I-type. Both profiles show that the levels of Fe2O3T, Al2O3 and TiO2 rise with increasing weathering intensity. On the other hand, SiO2, CaO, MgO, Na2O, and K2O are decreased. Light-REE are more abundant than heavy-REE in all samples. The studied profiles reveal differences in the type of Eu anomaly, intensity Light-REE against heavy-REE, and the character of heavy-REE normalization.